Role of RNA m6A expression profile in progression of renal fibrosis - CHEN Jing; ZHANG Han; GU Yu-lu; DING Xiao-qiang; ZHANG Xiao-yan (Linchuang shenzangbing zazhi)
Objective To investigate the expression profile of RNA m6 A in renal fibrosis model of unilateral ureteral obstruction（UUO） mice and conduct its related bioinformatics analysis,so as to provide theoretical basis and experimental basis for further study on the change and mechanism of RNA m6 A in renal fibrosis.Methods C57 BL/6 UUO mouse model of renal fibrosis was established by unilateral ureteral ligation.They were randomly divided into sham and UUO group.At first,mass-spectrography was used to detect the changes of RNA m6 A contents in the kidney in the two groups.Then,methylated RNA immunoprecipitation（MeRIP） sequencing method was used to detect the changes of the modified sites of RNA m6 A in the two groups.After identifying presence of abnormal modification of RNA m6 A in renal fibrosis,we further screened out regulation enzymes associated with RNA m6 A in the kidney through real quantitative RT-PCT.Results Compared with the sham group,the RNA m6 A content in the kidney in the UUP group was elevated significantly.MeRIP sequencing analysis showed a total of 1352 sites with methylation level differences >1.5 times among them,including 906 up-regulating ones and 446 down-regulating ones,involved the genes associated with cell junction,inflammatory response,transdifferentiation,calcium binding,cell adhesion,vascular calcification,etc.RT-PCR results suggested that RNE methylase METTl14 might be a key regulatory enzyme.Conclusions The epigenetic regulation of RNA m6 A is involved in the development of renal fibrosis,and METTl14 may be the key regulatory enzyme.